Polluted fog can increase level of metal contamination in dwarf shrubs in High Arctic - Opała-Owczarek, Magdalena; Phulara, Mohit; Sitko, Krzysztof; Migała, Krzysztof; Szymański, Wojciech; Węgrzyn, Michał; Korabiewski, Bartosz; Owczarek, Piotr (Polish Polar Research, 2026)
The impact of pollutants on plants and their spatial distribution, whether from distant locations or local sources, is not fully understood in the High Arctic. This is particularly relevant to the accumulation of pollutants in plants growing at different altitudes. This study aims to determine the concentration of metals in the area around Longyearbyen, which is Svalbard's largest emitter of pollutants, at different altitudes. Samples of polar willow, including both shoots and roots, were collected at three sites located at altitudes of 75–461 m a.s.l. Soil samples were also collected for testing to assess the chemical composition of topsoil and the concentration of exchangeable cations and plant-available elements. We analyzed the accumulation of Cd, Cu, Mg, Mn, Fe and Zn in bark and xylem. Our research indicates that pollutant levels in plants growing at altitudes of 420–461 m a.s.l. are ca. 2–3 times higher than in the valley. In addition, we found that the concentration of pollutants in the bark often exceeds > 10 times the values specified for wood, especially in the case of Fe, Mn and Zn. Dendrochronological studies confirm high concentrations of pollutants at higher altitudes. At polluted sites, the width of the growth rings was almost half that found in the less polluted valley. Plants at an altitude of > 420 meters are more frequently exposed to fog and low clouds, which directly supply them with polluted water.